SOSIALISASI FOCUS GROUP DISSCUSION TERKAIT KELENGKAPAN DOKUMEN REKAM MEDIS BERDASARKAN PMK NO. 31 TAHUN 2019 TENTANG SISTEM INFORMASI PUSKESMAS DI PUSKEMAS TALUN KENAS - Elisabeth Dame Manalu; Selamat Ginting; Diana Sinulingga (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
To improve the quality of health services and assess the performance of a good and efficient Puskesmas is one of the results of filling out medical records in inpatient rooms (Depkes RI, 2005). The technical guideline for managing medical records at a Puskesmas is to regulate the process of recording medical record activities starting at the time of patient acceptance, recording while the patient is receiving medical services to handling medical record files. A medical record file is a form of a health information system in a health center. In PERMENKES No. 31 of 2019, the Puskesmas Information system is an arrangement that provides information to assist the decision-making process in implementing the management of the Puskesmas in achieving its activity targets. Recording is a series of activities to document the results of observations, measurements, and/or calculations at each step of the health effort carried out by the Puskesmas. Furthermore, data collection by observation was carried out to determine the process of filling out medical records and the results of filling out medical records. The results of the analysis will be made into a strategic issue which will then be followed up with a focus group discussion, so that it can produce recommendations in an effort to improve the completeness of medical records at the Talun Kenas Health Center.